ANALISIS PROSEDUR PENGELOLAAN SURAT MASUK DAN SURAT KELUAR DI DINAS KEPENNDUDUKAN DAN PENCATATAN SIPIL KABUPATEN TANAH DATAR - Lailatul Rahmi; Armida Silvia; Menik Kurnia Siwi (Universitas Negeri Padang, 2018)
This research aims to determine the management procedures, incoming and outgoing mail in the Department ofPopulation and Civil Registration Tanah Datar. This research was a descriptive research with qualitative methods.The types of data used in this study were a primary data and secondary data. Data collection techniques used:observation, interviews, and documentation. Technique authenticity of data used triangulation techniques.Determination of informants of this research used purposive sampling technique. The results of this research weremanagement procedures, incoming and outgoing mail was not optimal for the management of the mail was not inaccordance with the guidelines used by the Department of Population and Civil Registration Tanah Datar. Obstaclesencountered in the management letter that was often receive supplementary letter, the rediscovery of the archiverequires a long time, and archival storage room was not yet available. From these results Office of Population andCivil Registration Tanah Datar, it is advisable to carry out management activities in accordance with the letter of theguidelines have been used, as well as an effective complementary equipment in the rediscovery of the archives, andheld a special space for archive storage.Keywords: Procedures, Inbox, and Outgoing Mail